2010
DOI: 10.1016/j.matbio.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-3 in articular cartilage is upregulated by joint immobilization and suppressed by passive joint motion

Abstract: Both underloading and overloading of joints can lead to articular cartilage degradation, a process mediated in part by matrix metalloproteinases (MMPs). Here we examine the effects of reduced loading of rat hindlimbs on articular cartilage expression of MMP-3, which not only digests matrix components but also activates other proteolytic enzymes. We show that hindlimb immobilization resulted in elevated MMP-3 mRNA expression at 6 hours that was sustained throughout the 21 day immobilization period. MMP-3 upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Previous studies display that reactive oxygen radicals induced by ionizing radiation may be responsible for the degradation of the physiologically important glycosaminoglycan hyaluronan [10,26,27]. Degradation of the proteoglycans and type II collagen present within the matrix of articular cartilage relates to mechanisms of various enzymes [2]. However, effects on these mechanisms are not sufficiently understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies display that reactive oxygen radicals induced by ionizing radiation may be responsible for the degradation of the physiologically important glycosaminoglycan hyaluronan [10,26,27]. Degradation of the proteoglycans and type II collagen present within the matrix of articular cartilage relates to mechanisms of various enzymes [2]. However, effects on these mechanisms are not sufficiently understood.…”
Section: Resultsmentioning
confidence: 99%
“…Cartilage is a joint lubricating tissue composed primarily of proteoglycans and type II collagen [1], both determining the mechanical properties of articular cartilage and the latter being critically important for the tissue integrity [2].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of MMP-3 is primarily regulated at the level of transcription, where the promoter of the gene responds to various stimuli, including growth factors, cytokines, tumor promoters and oncogene products (20). MMP-3 expression is also induced in response to local conditions, such as mechanical loading (21) and inflammation (22).…”
Section: Matrix Metalloproteinase-3mentioning
confidence: 99%
“…Animal studies have demonstrated physiologic loading of joints exerts beneficial effects by suppressing the activity of proteolytic enzymes in healthy and arthritic rats. Passive joint motion prevented cartilage destruction due to inactivity and downregulated MMPs 1 and 3 (Leong et al 2010;Leong et al 2011). In antigen-induced rabbits, passive motion prevented proteoglycan loss and suppressed expression of MMP-1 (Ferretti et al 2005;Ferretti et al 2006).…”
Section: Anti-catabolic Effects Of Exercise On Cartilagementioning
confidence: 94%
“…Elevated levels of pro-inflammatory cytokines such as IL-1 and TNF-stimulate production of proteolytic enzymes matrix metalloproteinases (MMPs) and A Disintegrin and Metalloproteinase with Thrombospondin Motifs (ADAMTS) which mediate the cartilage destruction process in RA (Sun 2010). Studies have demonstrated physiological loading suppresses MMP and ADAMTS expression in both inflamed and noninflamed joints to exert protective effects on the synovium and articular cartilage (Ferretti et al 2005;Ferretti et al 2006;Leong et al 2010). The most recent progress on these mechanotransduction pathways which regulate the loading-induced anti-inflammatory and anti-catabolic responses will be presented, as well as possible crosstalk between these two pathways.…”
mentioning
confidence: 99%